Higher spring phenological sensitivity to forcing temperatures of Asian compared to European tree species under low and high pre-chilling conditions - Walde, Manuel G.; Wu, Zhaofei; Fox, Tom; Baumgarten, Frederik; Fu, Yongshuo H.; Wang, Shuxin; Vitasse, Yann (Frontiers in Forests and Global Change, 2022)
Winter chilling, spring forcing temperature and photoperiod are the most important drivers explaining the spatial and temporal variability of spring phenology in temperate trees. However, how these factors interact with each other on dormancy release and spring budburst date remains unclear and varies greatly depending on species. Our knowledge is also limited as to whether heat accumulation of forcing temperatures that trigger bud break in spring is a linear or non-linear process. Here, we aimed at experimentally quantifying the effect of chilling, forcing, photoperiod and their interactions on the budburst dates of nine different temperate tree species from East Asia (near Beijing, China) and Central Europe (near Zurich, Switzerland), including six phylogenetically related species (same genus). We conducted a full factorial experiment in climate chambers using two chilling (low and high, i.e., 0 vs. 56 days at 2°C after sampling at the end of December), four forcing (5, 10, 15, and 20°C), and two photoperiod (8 vs. 16 h) treatments simultaneously in Beijing and Zurich. We found that species growing near Beijing responded more readily to forcing conditions than species of the same genus growing near Zurich regardless of chilling treatment. Budburst timing of most species but European beech was marginally, if at all, affected by photoperiod. Furthermore, our results suggest that linear heat accumulation, as commonly used with the growing degree hours (GDH) model, could result in accurate prediction of budburst date depending on the temperature threshold used as a basis for heat accumulation. Our results also demonstrate the important role of chilling in shaping the sensitivity and rate of forcing accumulation to trigger budburst and suggest that species-specific sigmoid relationship for accumulating heat that accounts for prior chilling exposure may yield better predictions of budburst dates. Our results suggest that deciduous trees may have adapted their chilling and forcing requirements in regards to the predictability of winter-spring transition and late spring frosts. A less predictable winter-spring transition, as observed in Central Europe, could have driven species evolution towards higher chilling and forcing requirements compared to species growing in a more predictable climate of Northeastern Asia. Our cross-continental experiment therefore suggests that the spring phenology of East Asian species is tighter coupled to spring forcing temperature than Central European forests.